An Experiment of Shear Strength Reinforced Geopolymer Concrete Beam Based High-Calcium Fly Ash with Varian Shear Span-to-Depth Ratio - Moh. Safi’i Mansur; Priyo Suprobo; Yuyun Tajunnisa; Auliagitta Kumala Apsari (Journal of Civil Engineering, 2023)
This study discusses geopolymer-reinforced concrete beam's shear strength capacity by experimental observation using high-calcium fly ash as the main binder. This study observed the influence of shear span per effective depth ratio due to the geopolymer concrete beam's shear behavior and strength capacity. Two beams are designed to have diagonal tensile cracks; hence the shear failure state could be obtained. Each beam has similar properties by 150 mm in width, 250 mm in height, 1800 mm in length, 2D16 as the flexure bar reinforcement, and stirrups of Ø6-250 with 20 mm concrete cover. The research employed the four-point load bending testing with the load span difference of each beam, which will later be the study variable. The things sought in this study include the peak load-deflection curve, the shear capacity that occurs in geopolymer concrete beams, and the shear capacity comparison with ACI 318-19. The results of the tests that have been carried out show that type A geopolymer-reinforced concrete beam was more ductile than type B beams, with a percentage difference of about 21.49% in deflection. The shear strength at the ratio a/d of 2 was 115,04 kN, and the ratio a/d of 2.5 was 89,00 kN. As well as a comparison of the shear strength of the test results with calculations according to ACI 318-19 shows a ratio of 1.69. So it can be concluded that ACI 318-19 calculations were conservative.